Pengaruh Motivasi, Kepuasan, dan Sikap Kerja terhadap Kinerja Karyawan di CafÃ© X Bogor - Subakti, Agung Gita (Bina Nusantara University, 2013)
HR management is an effort to integrate the needs of personnel with organizationâs objectives to increase the contribution that can be given by the employees of the organization towards the achievement of goals. This research examined the effect of motivation, job satisfaction, and working attitude to job performance on CafÃ© Xâs employees, Bogor. The use of these variables is expected to solve the performance problem on the employees. The respondents of this study were 25 employees using sampling techniques survey. The Research method used are literature and empirical (survey) approach, and the multiple regression statistical analysis. The analysis showed that working attitude and motivation have a positive effect on employee performance, with the closeness of the relationship in the medium category. To working attitude variable, the highest dimension is cognitive component and the lowest is behavior component. To motivation variable, the highest dimension is physical dimension and the lowest is self-actualization. While job satisfaction does not significantly influence on employee performance. Compensation becomes the major factor to dissatisfaction and the lowest is promotion factor. These empirical findings indicate that the restaurant management needs an improvement in order to improve the performance of employees, especially to evaluate compensation policies and the provision of incentives.